ANALISIS FAKTOR YANG MEMPENGARUHI MINAT KUNJUNGAN PEMERIKSAAN INSPEKSI VISUAL ASAM ASETAT (IVA) PADA WANITA USIA SUBUR DI PUSKESMAS SIPAHUTAR TAHUN 2019 - Esther Siringo-ringo (Pusat Riset dan Inovasi Nasional, 2021)
Cervical cancer is a malignancy in the cervix or cervical uterus. Efforts made to detect cervical cancer include cervical cancer screening with Inspection of Visual Acetate (IVA) method. The purpose of this study was to analyze the factors that influenced the interest in visiting the inspection of Visual Acetate (IVA) Inspection by Productive age women in Sipahutar Health Center in 2019. The type of this study was the Cross Sectional method. The population in the study was productive age women in Sipahutar Public Health Center. The eligible women were 4408 women and 96 women were taken as sample . The results of the study stated that there was a significant influence between age and interest in visiting; education; knowledge; access to information; health services; support of health and socio-cultural personnel with p value <0.05. The variable that most influenceing was the interest in IVA examination visits is access to information with a value of Rp. 95,615. It is hoped that productive age women will increase its knowledge about the dangers of cervical cancer and participate in the early detection of cervical cancer using the IVA method at the health care facility.